Bdellovibrio bacteriovorus HD100 guards against Pseudomonas tolaasii brown-blotch lesions on the surface of post-harvest Agaricus bisporus supermarket mushrooms - Saxon, Emma B (BioMed Central, 2014)
BACKGROUND: Pseudomonas tolaasii is a problematic pathogen of cultured mushrooms, forming dark brown ‘blotches’ on mushroom surfaces and causing spoilage during crop growth and post-harvest . Treating P. tolaasii infection is difficult, as other, commensal bacterial species such as Pseudomonas putida are necessary for mushroom growth, so treatments must be relatively specific. RESULTS: We have found that P. tolaasii is susceptible to predation in vitro by the δ-proteobacterium Bdellovibrio bacteriovorus. This effect also occurred in funga, where B. bacteriovorus was administered to post-harvest mushroom caps before and after administration of the P. tolaasii pathogen. A significant, visible improvement in blotch appearance, after incubation, was observed on administration of Bdellovibrio. A significant reduction in viable P. tolaasii cell numbers, recovered from the mushroom tissue, was detected. This was accompanied by a more marked reduction in blotch severity on Bdellovibrio administration. We found that there was in some cases an accompanying overgrowth of presumed-commensal, non-Pseudomonas bacteria on post-harvest mushroom caps after Bdellovibrio-treatment. These bacteria were identified (by 16SrRNA gene sequencing) as Enterobacter species, which were seemingly resistant to predation. We visualised predatory interactions occuring between B. bacteriovorus and P. tolaasii on the post-harvest mushroom cap surface by Scanning Electron Microscopy, seeing predatory invasion of P. tolaasii by B. bacteriovorus in funga. This anti-P. tolaasii effect worked well in post-harvest supermarket mushrooms, thus Bdellovibrio was not affected by any pre-treatment of mushrooms for commercial/consumer purposes. CONCLUSIONS: The soil-dwelling B. bacteriovorus HD100 preys upon and kills P. tolaasii, on mushroom surfaces, and could therefore be applied to prevent spoilage in post-harvest situations where mushrooms are stored and packaged for sale.